2011
DOI: 10.2340/00015555-0959
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and Safety of Biological Therapies for Psoriasis in Daily Clinical Practice: A Study of 103 Italian Patients

Abstract: Studies comparing the safety and tolerability of biological therapies for psoriasis in the long-term and in daily clinical practice are lacking. Most published studies are of selected patients with short-term (3-6 months) follow-up. We performed a retrospective cohort study of 103 patients in order to describe the frequency and the clinical features of adverse events, and to evaluate and compare the tolerability and safety of efalizumab, etanercept, infliximab, and adalimumab in clinical practice. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
(25 reference statements)
0
25
2
Order By: Relevance
“…Mention must also be made of our sustained efficacy results, with 13 patients with PASI90 after 4 years of treatment, 11 patients with PASI 90 after 5 years, and three patients with PASI90 after 6 years, respectively, as well as the absence of important side effects. These data are even discreetly better than those published by other authors (20,(22)(23)(24). By way of conclusion, we would like to emphasize that they demonstrate a greater efficacy of etanercept in regular clinical practice versus outcomes published on pivotal studies on the drug (25)(26)(27).…”
Section: Discussionmentioning
confidence: 39%
“…Mention must also be made of our sustained efficacy results, with 13 patients with PASI90 after 4 years of treatment, 11 patients with PASI 90 after 5 years, and three patients with PASI90 after 6 years, respectively, as well as the absence of important side effects. These data are even discreetly better than those published by other authors (20,(22)(23)(24). By way of conclusion, we would like to emphasize that they demonstrate a greater efficacy of etanercept in regular clinical practice versus outcomes published on pivotal studies on the drug (25)(26)(27).…”
Section: Discussionmentioning
confidence: 39%
“…The majority of psoriasis patients suffer from mild disease (PASI ≤10), which can often be managed with topical agents, while phototherapy or systemic therapies are usually used for patients with moderate-to-severe psoriasis (PASI >10). In the last decade, significant advances in the management and treatment of psoriasis have been made with the introduction of biologic agents,14,15 which have shown greater clinical benefit than traditional systemic therapies 1622…”
Section: Introductionmentioning
confidence: 99%
“…1921 Nevertheless, studies have demonstrated annual treatment discontinuation rates of 15–25% among traditional systemic therapies and phototherapy. 18 Studies on biologics also showed a progressive loss of treatment persistence, with first-year attrition rate of 10–15%.…”
Section: Introductionmentioning
confidence: 99%
“…18 Studies on biologics also showed a progressive loss of treatment persistence, with first-year attrition rate of 10–15%. 19, 20 As a composite surrogate marker of treatment efficacy, safety, tolerability, and overall satisfaction, treatment persistence in moderate-to-severe psoriasis is low and may contribute to suboptimal treatment response and increased healthcare utilization. 1720 …”
Section: Introductionmentioning
confidence: 99%